Clinical and molecular insights into cardiovascular disease in psoriatic patients and the potential protective role of apremilast - Barbarroja, Nuria; López-Medina, Clementina; Escudero-Contreras, Alejandro; Arias-de la Rosa, Iván (Frontiers in Immunology, 2024)
Psoriatic disease, encompassing both psoriasis (Pso) and psoriatic arthritis (PsA), is closely intertwined with a significantly elevated risk of developing cardiovascular diseases. This connection is further compounded by a higher prevalence of cardiometabolic comorbidities, including type 2 diabetes, obesity, insulin resistance, arterial hypertension, and dysregulated lipid profiles. These comorbidities exceed the rates seen in the general population and compound the potential for increased mortality among those living with this condition. Recognizing the heightened cardiometabolic risk inherent in psoriatic disease necessitates a fundamental shift in the treatment paradigm. It is no longer sufficient to focus solely on mitigating inflammation. Instead, there is an urgent need to address and effectively manage the metabolic parameters that have a substantial impact on cardiovascular health. Within this context, apremilast emerges as a pivotal treatment option for psoriatic disease. What sets apremilast apart is its dual-action potential, addressing not only inflammation but also the critical metabolic parameters. This comprehensive treatment approach opens up new opportunities to improve the well-being of people living with psoriatic disease. This review delves into the multifaceted aspects involved in the development of cardiovascular disease and its intricate association with psoriatic disease. We then provide an in-depth exploration of the pleiotropic effects of apremilast, highlighting its potential to simultaneously mitigate metabolic complications and inflammation in individuals affected by these conditions.